2013
DOI: 10.1016/j.ijhydene.2012.07.026
|View full text |Cite
|
Sign up to set email alerts
|

Characterization and activity test of commercial Ni/Al2O3, Cu/ZnO/Al2O3 and prepared Ni–Cu/Al2O3 catalysts for hydrogen production from methane and methanol fuels

Abstract: Khzouz, M. et al. (2013). Characterization and activity test of commercial Ni/Al203, Cu/ZnO/Al203 and prepared NieCu/Al203 catalysts for the hydrogen production from methane and methanol fuels. A comprehensive comparison between these two fuels is established in terms of reaction conditions, fuel conversion, H2 selectivity, CO2 and CO selectivity. The prepared catalyst showed low selectivity for CO in both fuels and it was more selective to H2, with H2 selectivities of 99% in methane and 89% in methanol reform… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
50
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(52 citation statements)
references
References 60 publications
2
50
0
Order By: Relevance
“…Previous work dealing with TPR studies on the reduction of Ni-Cu/y-Al 2 O 3 catalysts suggested that the addition of Cu to Ni precursors can dramatically decrease the reducing temperature of Ni oxides, and might markedly enhance the reducibility of the mixed oxide catalysts [23,38,39]. The promotion effect was stronger as the amount of Cu introduced increased [40][41][42].…”
Section: Tprmentioning
confidence: 95%
“…Previous work dealing with TPR studies on the reduction of Ni-Cu/y-Al 2 O 3 catalysts suggested that the addition of Cu to Ni precursors can dramatically decrease the reducing temperature of Ni oxides, and might markedly enhance the reducibility of the mixed oxide catalysts [23,38,39]. The promotion effect was stronger as the amount of Cu introduced increased [40][41][42].…”
Section: Tprmentioning
confidence: 95%
“…It has been reported that the introduction of Cu in the catalyst formulation suppresses coke deposition and the sintering of the active phase, in steam/dry reforming of hydrocarbons [44][45][46][47][48][49][50]. Fornasiero et al [45] have comprehensively studied the methanol and ethanol steam reforming activity of a series of Ni x Cu y /Al 2 O 3 catalysts prepared by wet-impregnation method.…”
Section: Ni Metal Particles Modified With Other Metals (Sn Cu Co Mmentioning
confidence: 99%
“…Several studies have suggested the use of thick coating or secondary coating as solution to overcome this problem [15,23,24]. 8 No significant weight change was observed during the initial test for the sponge as presented in [25]. However, it started to decompose in a two-step manner with an obvious steep decrease at approximately 250-330 ºC due to the decomposition of urethane bonds; the second decrease happened between 350 ºC and 420 ºC, attributed to loss of ester groups [26].…”
Section: Process Of Coatingmentioning
confidence: 99%
“…Besides that, oxide (Al 2 O 3 ) and base metal catalyst (Ni/SiC and Ni/Al 2 O 3 ) were previously used in partial oxidation of methane [7,8].…”
Section: Introductionmentioning
confidence: 99%